Oyster beds in the United Arab Emirates: Important fishing grounds in need of protection. (September 2022) - Bento, Rita; Jabado, Rima W.; Sawaf, Moaz; Bejarano, Ivonne; Samara, Fatin; Yaghmour, Fadi; Mateos-Molina, Daniel
Abstract: There is scarce information on the current importance of oyster beds as fishing grounds in the United Arab Emirates (UAE). This study aims to understand the socio-economic value of oyster bed fisheries through questionnaire-based surveys with fishers. Of 106 Emirati fishers interviewed, 67 % use oyster beds due to the proximity to shore, better catch quality, and species abundance. Oyster bed fisheries are recreational and commercial, with handline and fish traps the most common used gears. They provide food for local consumption and cash income. All respondents noticed a fish abundance and size decrease throughout the last decade. Fishers suggest establishing marine protected areas and updating fishing regulations to improve fishing stock status. During the Covid-19 pandemic, oyster fisheries increased, highlighting the value of these fishing grounds for food availability. These fisheries support the local economy and heritage, and urgently need management to ensure the protection of these often-overlooked habitats. Highlights: Oyster beds provide food and income for local communities in the UAE. Fishers were interviewed to assess their importance as fishing grounds. Fishers indicated reductions in oyster beds' area and fish abundance and size. Fishing activities in oyster beds habitats increased during the Covid-19 pandemic. Management actions are needed to preserve oyster bed habitats and fisheries.